Development of a Single-Phase PWM-Based Dc-To-Dc Converter for Electric Bicycle - Ahmad Almathnani, Ali Omar (2000)
An electric bicycle is a bicycle that can be operated automatically or manually. The main difference between an electric bicycle and a normal bicycle is that the speed controller of the DC motor attached to the electric bicycle can control the speed of the electric bicycle. It is suitable for a short distance transportation mode. The advantages of the electric bicycle include better speed performance, no pollution, convenient to use, inexpensive and require less maintenance. The objective of this project was to develop a single-phase PWM-based DC-to-DC converter for an electric bicycle. The electric bicycle consisted of a lead-acid battery, a DC-to-DC converter, a permanent magnet DC motors and the bicycle itself. The single-phase converter used pulse width modulation (PWM) switching with an Insulated Gate Bipolar Transistor (IGBT) as power device. The speed of the motors was controlled through the duty cycle of the PWM signal. A protection circuit for the converter was also included in the design. A voltage level monitoring system was developed for the electric bicycle to monitor its lead-acid battery voltage level. A new bicycle pulley system was designed and constructed to integrate mechanical and electrical parts of the bicycle. Results of the experimental and simulation showed that there was a good agreement between the hardware and the software. This indicates that the single-phase PWM based DC-to-DC converter was successfully developed.